Mitigating Phytophthora foot rot and slow decline diseases of black pepper through the deployment of bacterial antagonists - Aravind, R Pervez, R S Bhai*, S J Eapen, A Kumar, R; K Sreeja, E M Varghese, P B Krishna & (Journal of Spices and Aromatic Crops, 2017)
Field trial was conducted at ICAR-IISR Experimental Farm, Peruvannamuzhi, Kozhikode district, Kerala, during 2008-2013 using IPM modules. Planting materials of black pepper were produced by raising two node runners cuttings treated with chemicals and bioagents. A plot having non-living standards in 3 x 2 m spacing was selected. Pits of 50 cm3 were made and buffered with lime and cow dung. Planting was done with three month old rooted plants where roots were primed with respective bacterium/chemical. The experiment was in RCBD with eight treatments viz., Pseudomonas aeruginosa (Bp 35) + Phorate, P. putida (Bp 25) + Phorate, P. fluorescence (IISR 6) (later identified as P.aeruginosa) + Phorate, Bacillus megaterium (Bp 17) + Metalaxyl Mz, Curtobacterium luteum (TC10) + Metalaxyl Mz, P. aeruginosa (IISR 853) + Metalaxyl Mz and Phorate + Metalaxyl Mz (chemical check) and an absolute control having no treatments. The differential treatments were imposed at planting in May and subsequent application in September and thereafter every year. Initial two years, plants were maintained weed free by plastic mulching. Commonly, shade and irrigation were provided during summer in the first two years and thereafter only mulching and irrigation were continued. All the plants were sprayed with ZnSO4 (0.25%), DAP (0.5%) and MgSO4 (0.25%) during May and September from second year onwards. For controlling ‘Pollu’ beetle (Longitarsus nigripennis) and anthracnose (Colletotrichum gloeosporioides), quinalphos (0.075%) + Bordeaux mixture (1%) was sprayed twice during September and November. Soil biological properties and pathogen population were monitored regularly. No foot rot incidence due to Phytophthora spp. could be noticed in any of the treatments till the end of the experimental period. However, nematode infection, manifested as yellowing of the vines, as well as nematode population showed a gradual increase. Among the treatments, C. luteum (TC 10) with Metalaxyl- Mz showed significant reduction in nematode population and also showed better performance in growth and yield.